2007
DOI: 10.1017/s0959774307000200
|View full text |Cite
|
Sign up to set email alerts
|

Building for the Dead: Events, Processes and Changing Worldviews from the Thirty-eighth to the Thirty-fourth Centuries cal. bc in Southern Britain

Abstract: Our final paper in this series reasserts the importance of sequence. Stressing that long barrows, long cairns and associated structures do not appear to have begun before the thirty-eighth century cal. bc in southern Britain, we give estimates for the relative order of construction and use of the five monuments analysed in this programme. The active histories of monuments appear often to be short, and the numbers in use at any one time may have been relatively low; we discuss time in terms of generations and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 53 publications
0
36
0
1
Order By: Relevance
“…Many such monuments do not seem to have been constructed before the 38th century cal BC Whittle et al 2011b). A possible comparison for Coldrum may be identified at Burn Ground in the Cotswolds (Smith & Brickley 2006;Dixon et al 2011), which may have been constructed in 4140-3760 cal BC (95% probable) or 3985-3875 cal BC (46% probable) or 3860-3790 cal BC (22% probable; start Burn Ground; Smith & Brickley 2006, fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many such monuments do not seem to have been constructed before the 38th century cal BC Whittle et al 2011b). A possible comparison for Coldrum may be identified at Burn Ground in the Cotswolds (Smith & Brickley 2006;Dixon et al 2011), which may have been constructed in 4140-3760 cal BC (95% probable) or 3985-3875 cal BC (46% probable) or 3860-3790 cal BC (22% probable; start Burn Ground; Smith & Brickley 2006, fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Without further chronological evidence for the local Medway monuments, or better dating of possibly related monuments from the continent (cf. Whittle et al 2011b), it is difficult to assess the role of Coldrum within early Neolithic monument traditions.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, they are a selection of the unwanted dead buried over a long period of time (Barber 1988). Fourth, the tombs had an interment use for only a very short period (Whittle et al 2007). …”
Section: Mass Burials On Orkneymentioning
confidence: 99%
“…While it is generally suggested that elevation and visibility are one of several cultural responses inherent in the tradition of tomb building (Whittle et al 2007), in the face of a devastating event, it is more likely that the need for rapid construction was the driving force.…”
Section: Mass Burials On Orkneymentioning
confidence: 99%